TRACING THE ROOTS OF CONSTRUCTION CONFLICTS: EXPLAINING PROBLEMS, PREFERENCES, AND PROCESS - Abdullah Mohammed Alshehri (Yanbu Journal of Engineering and Science, 2021)
The construction industry is continuously struggling to resolve the conflicts equitably and economically. Therefore, the present study aims to trace the roots of construction conflicts by explaining problems, preferences, and processes associated with the construction industry. Quantitative research design has been employed and 116 owners, constructors, consultants, and stakeholders were recruited because of their direct involvement in the construction industry. A questionnaire was distributed among the respondents to trace the problems, preferences, and processes associated with conflicts the construction industry. The results showed that that lack of communication and coordination, contract provisions, ambiguities, bid rigging, contracting classification system, unforeseen ground conditions, and discrepancies were major reasons of conflict. The study has concluded that productivity of construction industry is significantly influenced through the implementation of realistic schedule and plan for the construction project.